Study of the stability of the mathematical model of the сoupled pendulums motion - Surhanova, Yuliia E.; Mikhlin, Yurii V. (Інститут проблем машинобудування ім. А. М. Підгорного НАН України, 2023)
The paper presents a study of the dynamics of the oscillatory dissipative system of two elastically connected pendulums in a magnetic field. Nonlinear normal vibration modes of the pendulum system are studied in the paper taking into account the resistance of the medium, and the damping moment created by the elastic element. A system with two degrees of freedom is considered. The masses of the pendulums in that system differ significantly, which leads to the possibility of localization of oscillations. In the following analysis, the mass ratio was chosen as a small parameter. For approximate calculations of magnetic forces, the Padé approximation, which satisfies the experimental data the most, is used. This approximation provides a very accurate description of magnetic excitation. The presence of external influences in the form of magnetic forces and various types of loads that exist in many engineering systems leads to a significant complication in the analysis of vibration modes of nonlinear systems. A study of nonlinear normal vibration modes in this system was carried out, one of the modes is a connected mode, and the second one is localized. Vibration modes are constructed by the multiples scales method. Both regular and complex behavior is studied when changing system parameters. The influence of these parameters is studied for small and significant ini tial angles of the pendulum inclination. An analytical solution, which is based on the fourth-order Runge-Kutta method, is compared to numerical simulation results. The initial conditions for calculating the vibration modes were deter mined by the analytical solution. Numerical simulation, which consists of constructing phase diagrams, trajectories in the configuration space and spectra, allows to estimate the dynamics of the system, which can be both regular and complex. The stability of vibration modes is studied using numerical analysis tests, which are an implementation of the Lyapunov stability criterion. The stability of vibration modes is determined by the estimation of orthogonal deviations of corresponding trajectories of vibration modes in configuration space.

У статті представлено дослідження динаміки коливальної дисипативної системи двох пружно пов’язаних маятників у магнітному полі. Досліджено нелінійні нормальні моди коливань маятникової системи з урахуванням опору середовища, моменту демпфування, створеного пружним елементом. Розглянуто систему з двома ступенями свободи, в якій маси маятників суттєво розрізняються, що приводить до можливості появи локалізації коливань. У наступному дослідженні співвідношення мас обрано як малий параметр. Для наближених розрахунків магнітних сил використовується апроксимація Паде, яка найбільше задовольняє експериментальним даним. Це наближення забезпечує дуже точний опис магнітного збудження. Наявність зовнішніх впливів у вигляді магнітних сил і різного типу навантажень, які існують в багатьох інженерних системах, значно ускладнює аналіз мод коливань нелінійних систем. Проведено дослідження нелінійних нормальних мод коливань у даній системі, причому одна з мод є пов’язаним режимом, а друга – локалізованою. Моди коливань побудовано методом багатьох масштабів. Вивчено як регулярну, так і складну поведінку при зміні параметрів системи. Вплив цих параметрів досліджено для малих і значних початкових кутів нахилу маятника. Аналітичний розв’язок, який базується на методі Рунге-Кутти четвертого порядку, порівняно з результатами чисельного моделювання. Початкові умови для розрахунку мод коливань визначалися аналітичним розв’язком. Чисельне моделювання, яке складається з побудови фазових діаграм, траєкторій у конфігураційному просторі й амплітудно-частотних характеристик, дозволяє оцінити динаміку системи, що може бути як регулярною, так і складною. Стійкість режимів коливань досліджено за допомогою тестів чисельного аналізу, які є реалізацією критерію стійкості Ляпунова. При цьому стійкість режимів коливань визначається шляхом оцінки ортогональних відхилень відповідних траєкторій режимів коливань у конфігураційному просторі.
Дослідження стійкості математичної моделі руху пов'язаних маятників
Keywords: coupled pendulums; magnetic forces; nonlinear normal vibration modes; the multiples scales method; stability; пов'язані маятники; магнітні сили; нелінійні нормальні моди коливань; метод багатьох масштабів; стійкість